A comprehensive study of the source, occurrence, and spatio-seasonal dynamics of 12 target antibiotics and their potential risks in a cold semi-arid catchment. (1st February 2023) - Ju, Hanyu; Liu, Ling; Liu, Xuemei; Wu, Yao; Li, Lei; Gin, Karina Yew-Hoong; Zhang, Guangxin; Zhang, Jingjie
Highlights: Spatio-seasonal dynamics of antibiotics in a high-latitude agricultural catchment. Concentrations of selected antibiotics were higher during freeze–thaw periods. ARGs were related to the half-life and lipophilicity of antibiotics. The mixture quotient risk map shows potential risks to the regional ecosystem. A hierarchical priority control list of antibiotics is recommended. Abstract: Antibiotics are widely consumed and are ubiquitous in aquatic ecosystems, such as in agricultural and fishery lake catchments, for prophylactic treatment. However, there are very few comprehensive studies reporting all seasonal occurrences, spatiotemporal dynamics, and risk assessments of antibiotics in agricultural lake catchments, especially in cold regions during the winter season. This study measured seasonality in the concentrations of 12 antibiotics belonging to seven different classes in the surface waters (tributary rivers and lakes) of the Chagan lake catchment in northeast China. All antibiotics were detected in most of the water samples across most seasons, with concentrations varying for different compounds, locations, and seasons. These levels were discussed in terms of the main sources at different sampling sites, including agriculture, fish farming, municipal wastewater, and others. In general, the highest concentrations of most compounds were observed during the freeze–thaw periods. The number of antibiotic resistance genes (ARGs) correlated with compound lipophilicity and half-life. Based on the ecological risks of antibiotics and the relative abundance of ARGs, a hierarchical control priority list (HCPL) of antibiotics was determined, considering four levels (critical, high, medium, and low). To further strengthen the control and effectively manage antibiotics, we highly recommend the reduction and selective use of veterinary antibiotics in winter and spring during the freeze–thaw periods in the Chagan lake catchment. Graphical abstract: Image, graphical abstract